Structure–property relationships in polyethylene based films obtained by blow molding as model system of industrial relevance. (January 2015) - Duraccio, Donatella; Mauriello, Amalia; Cimmino, Sossio; Silvestre, Clara; Auriemma, Finizia; De Rosa, Claudio; Pirozzi, Beniamino; Mitchell, Geoffrey Robert
Graphical abstract: Highlights: The structure–property relationships of PE-based films by blow molding are studied. Model mixtures of a metallocene-made LLDPE and LDPE are used. Mechanical properties are related to molecular branching, structure and morphology. H2 O and O2 permeability depend on the thickness of amorphous layer in lamellar stacks. Abstract: A method for the study of structure–property relationships of polyethylene (PE)-based films of potential use in food packaging has been set up. The approach has been demonstrated in the case of films obtained by blow-molding using model mixtures of two different polyethylenes, namely a metallocene-made grade of linear low density polyethylene (mLLDPE) and a low density polyethylene (LDPE). We show that physical properties important for numerous applications of these films, such as water vapor and oxygen permeability, toughness and stress strength, are related to the molecular structure and structural and morphological parameters of the blends, in particular, thickness of amorphous layers in lamellar stacks, lamellar thickness, lamellar twisting, and degree and type of branching.